The definitive Drucker - Edersheim, Elizabeth Haas.; Drucker, Peter F. (Peter Ferdinand), 1909-2005. (New York : McGraw-Hill, 2007)
"For consultant Edersheim, a request directly from Peter Drucker to write about his life's work was a dream come true. For 16 months, Edersheim had unprecedented access to Drucker, talking with the father of modern management about business practices, economic changes, and contemporary trends--many of which he had predicted decades ago. During this period, she also interviewed top executives about Drucker's influence; they in turn gave their views on his management wisdom. This book delivers the most updated and comprehensive view of Drucker's contribution to the discipline of management over the past 75 years, updated for the modern business approach with new applications of his timeless principles.--From publisher description."--From source other than the Library of Congress
Doing business in the Lego world -- The customer : joined at the hip -- Innovation and abandonment -- Collaboration and orchestration -- People and knowledge -- Decision making : the chassis that holds the whole together -- The twenty-first-century CEO.
Includes bibliographical references and index.
"Books by Peter F. Drucker": p. 271-273.
Keywords: Management; Leadership